PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA AMIL ZAKAT YAYASAN YATIM MANDIRI (MELALUI PENDEKATAN ALEN MEYER) - Anita Roosmawarni (Jurnal Ekonomi dan Manajemen, 2016)
This study aims to determine the organizational commitment, performance, and the influence of the three components of organizational commitment, namely affective commitment, continuous commitment and normative commitment to performance ZIS Consultant Amil Zakat Foundation Yatim Mandiri. The are 78 ZIS Consultant in population, and based on the formula Slovin obtained a sample of 65. The research method uses quantitative methods. Data were collected by questionnaire and analyzed with SPSS 20.0 application. Research results revealed that organizational commitment and performance ZIS Consultant Amil Zakat Foundation Yatim Mandiri is at a high category. Organizational commitment have significant and positive influence on the performance of ZIS Consultant with the contribution of the effect of 60%. Affective commitment most dominant influence on the performance of ZIS Consultant with 19.98% contribution influences.